Utilization of Organic Waste to Improve Land Productivity Sustainably in Nagari Kudu Gantiang - Yanti, Nika Rahma; Sari, Silvia Permata; Juliandri, Irvan; Salihat, Rera Aga (Institute of Research And Community Service, Andalas University / LPPM Universitas Andalas, 2025)
Nagari Kudu Gantiang is one of the nagari where most residents are engaged in agriculture and livestock farming. However, the utilization of organic waste such as crop residues and livestock manure has not been optimized. Agricultural waste is often discarded or openly burned, leading to environmental pollution, while farmers remain highly dependent on chemical fertilizers whose prices continue to increase. Based on these conditions, this community service program aimed to enhance the capacity of the women’s PKK group in processing organic waste into compost as an effort to promote sustainable agriculture. The methods included counseling, participatory discussions, and compost-making demonstrations using agricultural residues, soil, and livestock manure with the addition of EM4 bio-activator. The activity was attended by 45 participants at the Nagari Kudu Gantiang Office Hall. The results indicated an increase in participants’ knowledge and skills in composting techniques, as well as growing awareness of environmentally friendly organic waste management. This program had a positive impact by encouraging household-level composting practices, reducing dependence on chemical fertilizers, and supporting sustainable land productivity at the nagari.